2021
DOI: 10.1177/00333549211041545
|View full text |Cite
|
Sign up to set email alerts
|

Severe Clinical Outcomes Among Adults Hospitalized With Respiratory Syncytial Virus Infections, New York City, 2017-2019

Abstract: Objectives Respiratory syncytial virus (RSV) causes substantial morbidity and mortality in older adults. We assessed severe clinical outcomes among hospitalized adults that were associated with RSV infections. Methods We performed a nested retrospective study in 3 New York City hospitals during 2 respiratory viral seasons, October 2017–April 2018 and October 2018–April 2019, to determine the proportion of patients with laboratory-confirmed RSV infection who experienced severe outcomes defined as intensive care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…In a study of nursing home residents with influenza reported by Barker et al , 25% of subjects with confirmed influenza infection had a decline in function 3–4 months after illness compared with a decline in 17% of matched control subjects (p = 0.04) 22 . Further highlighting pre‐hospitalization living situation as an important predictor, we recently found that patients living in a SNF prior to a RSV‐associated hospitalization were 4.4 times more likely to have severe clinical outcomes (composite outcome: ICU care, mechanical ventilation, and death) compared with community‐dwelling adults 23 …”
Section: Discussionmentioning
confidence: 91%
“…In a study of nursing home residents with influenza reported by Barker et al , 25% of subjects with confirmed influenza infection had a decline in function 3–4 months after illness compared with a decline in 17% of matched control subjects (p = 0.04) 22 . Further highlighting pre‐hospitalization living situation as an important predictor, we recently found that patients living in a SNF prior to a RSV‐associated hospitalization were 4.4 times more likely to have severe clinical outcomes (composite outcome: ICU care, mechanical ventilation, and death) compared with community‐dwelling adults 23 …”
Section: Discussionmentioning
confidence: 91%
“…Living situation was classified as living independently at home, living at home with assistance from family members or home health aide or residing in an assisted living facility, or living in a rehabilitation or skilled nursing facility. 16 Patients transferred from acute-care hospitals or who were homeless were excluded from assessment of living situation at admission.…”
Section: Data Collection and Outcomesmentioning
confidence: 99%
“…For those who survived, living situation at discharge and changes in living situation from admission to discharge that reflected the need for increased support (eg, living independently at admission versus discharge to a skilled nursing facility) were determined as previously described. 16 Patients who died, were transferred to another acute-care hospital, or were not eligible for the analysis of living situation at admission were excluded from the analysis of changes in living situation. Readmission within 30 days of discharge was also assessed.…”
Section: Data Collection and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other recent studies indicate that the burden of RSV disease may be even greater than that of influenza in hospitalized older adults [ 11–13 ]. Older adults living in long-term care facilities (LTCFs) are known to experience a high burden of respiratory diseases [ 14 ], and several studies have shown that the risk of severe RSV infection is higher among older adults living in LTCF settings than in adults in community-dwelling (CD) [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%